Efficient and stable lithium battery negative electrode slurry as well as preparation method and application thereof
By using specific ratios of graphite, silicon oxygen and other materials in lithium-ion batteries and glue preparation technology, the dispersion and stability of the negative electrode slurry in water is solved, and higher battery performance and safety are achieved, and the expansion of The application range of lithium-ion batteries.
Patent Information
- Application Number
- CN202411162388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-24
AI Technical Summary
The negative electrode slurry of existing lithium-ion batteries is not easily dispersed in water and has poor stability, resulting in a decrease in battery discharge platform, a decrease in charge and discharge cycle ratio and an inability to increase the volume-energy ratio, limiting the scope of use of the battery.
Using a highly efficient and stable lithium battery negative electrode slurry, including graphite, silicon oxygen, conductive agent, carboxymethylcellulose sodium and suspension agent, the viscosity and dispersion uniformity are adjusted through a specific glue preparation and infiltration and stirring process to form Highly efficient negative electrode slurry.
It achieves a higher discharge platform, better cycle capacity retention rate, meets 55℃ high-temperature short circuit safety and higher volume-energy ratio, widens the use range of lithium-ion batteries.
Smart Images

Figure CN119181804A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a highly efficient and stable negative electrode slurry for lithium batteries and a preparation method and application thereof. Background Art
[0002] With the continuous advancement of technology, modern mobile devices are becoming more and more diverse, and as the main energy supply component of mobile devices (lithium-ion batteries), they are receiving more and more attention and attention from the public. The competition in the lithium-ion battery market is becoming increasingly fierce. In order to enhance their competitiveness, major manufacturers are constantly improving battery performance. High discharge platform, fast charge and discharge, and high volume energy ratio are the mainstream development trends of the subsequent industry.
[0003] At present, the negative electrode slurry manufacturing of lithium-ion batteries is composed of adhesives, conductive carbon black, graphite active materials and solvents. The preparation of negative electrode slurry includes a series of process processes such as mixing, dissolving and dispersing between solid and solid, liquid and solid materials, and this process is accompanied by changes in temperature, viscosity, environment, etc. The main material of the negative electrode is generally graphite or silicon-based materials. These materials are non-polar substances, not easy to disperse in water, and easy to re-agglomerate after dispersion in water. Therefore, the negative electrode slurry has the problems of not being easy to disperse evenly, and the stability after dispersion is not very good, easy to settle, affecting the screening and coating uniformity of the slurry; and once there is a problem with the negative electrode slurry, it will cause the battery discharge platform to decrease, the charge and discharge cycle rate to decrease, the 55°C high temperature short circuit safety to decrease, and the volume energy ratio cannot be further improved. These problems have caused restrictions on the wider use of batteries.
[0004] Therefore, being able to provide an efficient and stable lithium battery negative electrode slurry and a preparation method thereof is an issue that needs to be urgently addressed by those skilled in the art. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a highly efficient and stable lithium battery negative electrode slurry and a preparation method and application thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A highly efficient and stable negative electrode slurry for a lithium battery, the negative electrode slurry comprising a solvent and a solid material, wherein the mass percentage of the solid material is 40-50%;
[0008] The solid material comprises the following raw materials in percentage by mass: 77-82% of graphite, 13.6-17.2% of silicon oxide, 0.8-1.2% of conductive agent, 0.05-0.1% of conductive paste, 1.35-1.5% of sodium carboxymethyl cellulose and 2.2-3.0% of suspending agent.
[0009] Preferably, the solvent is water and NMP, and the amount of NMP added is 1-4% of the mass of the solid material.
[0010] Preferably, the viscosity of the negative electrode slurry is 2000-4000 mPa.s.
[0011] Preferably, the suspending agent is SBR.
[0012] According to the above-mentioned method for preparing a highly efficient and stable negative electrode slurry for a lithium battery, the method comprises the following specific steps:
[0013] (1) Weighing raw materials: weighing raw materials of negative electrode slurry according to the mass percentage;
[0014] (2) Preparation of glue solution: CMC and water are mixed and then glued to obtain glue solution;
[0015] (3) Preparation of graphite pre-slurry: After dry powder mixing of graphite and part of the conductive agent, part of the glue is added for primary infiltration and stirring; then part of the conductive slurry is added for secondary infiltration and stirring; finally, water is added for viscosity adjustment to 6000-6500 mPa.s to obtain graphite pre-slurry;
[0016] (4) Preparation of silicon oxide pre-slurry: After dry powder mixing of silicon oxide and the remaining conductive agent, a portion of the glue solution is added for primary wetting and stirring; then the remaining conductive slurry is added for secondary wetting and stirring; finally, water is added for viscosity adjustment to 6000-6500 mPa.s to obtain silicon oxide pre-slurry;
[0017] (5) Liquid fusion: The graphite pre-slurry and the silicon oxide pre-slurry are mixed and stirred for liquid dissolution. After completion, the remaining glue solution is added for dilute glue stirring, and then the water is added for viscosity adjustment to 2000-4000 mPa.s. Finally, a suspending agent is added in sequence for suspension stirring and NMP is added for inversion degassing to obtain a negative electrode slurry.
[0018] The negative electrode slurry preparation of the present invention is divided into four steps. First, CMC is prepared into a glue solution, so that the powdered CMC is used in the subsequent slurry preparation in liquid form, which increases the dispersion effect of CMC and enhances the stability of the slurry.
[0019] Secondly, in the preparation process of graphite pre-slurry and silicon oxide pre-slurry, the corresponding materials are added in different slurry states of solid-slightly wet-mud-thin mud, which not only increases the dispersion uniformity of graphite or silicon oxide and conductive agent, but also partially introduces the binder into the mixed system in the slightly wet state of the slurry, which enhances the dispersion effect of the binder and the bonding effect of the binder; and after the first infiltration and stirring, a certain amount of conductive slurry is added to the slightly wet mixture for further infiltration and stirring, which makes the graphite or silicon oxide, conductive agent and binder more evenly dispersed on the one hand, and on the other hand, the stirring resistance in the slightly wet state of the slurry is small but there is a certain friction resistance. At this time, the addition of conductive slurry will not cause the conductive slurry to be unable to be fully dispersed or the shear force is too large to break the carbon tubes in the conductive slurry and fail, and will not cause the conductive slurry to agglomerate and be unable to be uniformly planned due to too small friction resistance; after the second infiltration and stirring, the slurry viscosity is adjusted by adding deionization, so that the slurry viscosity is between 6000-6500mpa.s, which is convenient for subsequent steps;
[0020] In addition, the present invention avoids the drawback that the two main materials of the negative electrode (silicon oxide and graphite) account for a large proportion and have a large difference in particle size distribution and cannot be fully fused and dispersed by fusing and stirring the graphite pre-slurry and silicon oxide pre-slurry prepared in the early stage in the liquid state. In addition, in the early stage of the pre-slurry preparation process, the viscosity of the two pre-slurries is adjusted to a similar viscosity state, so that the two pre-slurries are more smoothly fused in this step, avoiding fusion bubbles caused by viscosity differences, and making the dispersion of various materials more uniform.
[0021] At the same time, by further adding glue to the slurry after the liquid-dissolving stirring and stirring it, on the one hand, the full dispersion of the components in the slurry is further enhanced, and on the other hand, the adhesive effect of the slurry is increased, so that the interaction between the components in the slurry is enhanced and the slurry is more stable; finally, by adding suspending agent and NMP to the slurry after the viscosity is adjusted to meet the requirements and stirring it, the stability and producibility of the slurry are enhanced, laying the foundation for the convenience of subsequent slurry production and the excellent electrochemical performance of the battery.
[0022] Preferably, the viscosity of the glue in step (2) is 2000-4000 mPa.s.
[0023] Preferably, in step (3), the amount of the conductive agent added is 4 / 5-5 / 6 of the total amount, the amount of the glue added is 2 / 5-5 / 12 of the total amount, and the amount of the conductive paste added is 4 / 5-5 / 6 of the total amount.
[0024] Preferably, the amount of the glue added in step (4) is 1 / 12-1 / 10 of the total amount.
[0025] Application of the efficient and stable lithium battery negative electrode slurry described above or the efficient and stable lithium battery negative electrode slurry obtained by the preparation method described above in the preparation of negative electrode sheets.
[0026] Application of the above-mentioned efficient and stable lithium battery negative electrode slurry or the above-mentioned efficient and stable lithium battery negative electrode slurry obtained by the preparation method in the preparation of lithium batteries.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides a highly efficient and stable negative electrode slurry for lithium batteries and a preparation method thereof. By using the negative electrode slurry obtained by the method of the present invention, a soft-pack lithium-ion battery prepared can achieve a higher discharge platform, a capacity retention rate of more than 80% for 1.5C rate charge and discharge-300 cycles, meet 55°C high-temperature short circuit, and a volume energy ratio of more than 550Wh / L, thereby effectively broadening the use range of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 A comparison diagram of discharge curves of batteries prepared in Example 1-2 and Comparative Example 1-2;
[0031] Figure 2 The cycle comparison curve diagram of the battery prepared in Example 1-2 and Comparative Example 1-2;
[0032] Figure 3 The figure is a rate comparison curve diagram of the batteries prepared in Example 1-2 and Comparative Example 1-2. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A highly efficient and stable negative electrode slurry for lithium batteries, wherein the negative electrode slurry solvent is deionized water and NMP (the amount of NMP added is 1% of the mass of the solid material), the solid material content is 47%, the slurry viscosity is 2500mpa.s, and the solid material contains the following percentages of raw materials: 80% of graphite (Inner Mongolia Sanxin S1), 15% of silicon oxide (Lianchuang: LCL14-1), 1.0% of conductive agent LI-20, 0.1% of conductive slurry (Haiwei Jiaye O2H017), 1.4% of CMC and 2.5% of suspending agent SBR;
[0036] The preparation of negative electrode slurry specifically includes the following steps:
[0037] (1) Weighing raw materials: weigh the raw materials according to the mass percentage of the negative electrode slurry;
[0038] (2) Preparation of glue solution: CMC and deionized water are added into the mixing barrel in a ratio of 1.4:98.6 and stirred. First, stir at low speed for 5 minutes, change the speed and stir for 10 minutes after cleaning, clean again, and then stir at high speed for 20 minutes. After high-speed stirring, observe that the glue solution is transparent and clear, and there are no glue particles in the glue solution. If there are residual undissolved glue particles in the glue solution, the glue application time is extended by 30-60 minutes accordingly. After the glue solution is qualified, vacuum degassing is carried out for 10 minutes before discharging. The final glue solution viscosity is 2500mpa.s.
[0039] (3) Preparation of graphite pre-slurry: Graphite and 5 / 6 of the conductive agent are added to a slurry mixing barrel for dry powder stirring; then, 5 / 12 of the glue is added and stirred for a first soaking; then, 5 / 6 of the conductive slurry is added for a second soaking and stirring; finally, deionized water is added for viscosity adjustment, and the final viscosity is 6320 mPa.s. The specific stirring process is shown in Table 1;
[0040] Table 1 Graphite pre-slurry stirring process parameters
[0041]
[0042] (4) Preparation of silicon oxide pre-slurry: Add silicon oxide and the remaining conductive agent into a slurry mixing barrel for dry powder stirring; then, add 1 / 12 of the glue solution and perform a first soaking stirring; then, add the remaining conductive slurry for a second soaking stirring; finally, add deionized water for viscosity adjustment, and the final viscosity is 6270 mPa.s. The specific stirring process is shown in Table 2;
[0043] Table 2 Silica pre-slurry mixing process parameters
[0044]
[0045] (5) Liquid fusion: Add graphite pre-slurry and silica pre-slurry into a slurry mixing barrel for liquid dissolution stirring; then, add the remaining glue solution and stir for dilute glue; then adjust the slurry viscosity by adding deionized water, and the final viscosity is 2500mpa.s; then, add the suspending agent SBR to the slurry after the viscosity adjustment is qualified and suspend and stir; finally, add NMP to the slurry after stirring and reverse degassing to obtain qualified negative electrode slurry. The specific stirring process is shown in Table 3;
[0046] Table 3 Silica pre-slurry mixing process parameters
[0047]
[0048] A lithium battery was prepared using the negative electrode slurry prepared in Example 1:
[0049] Including positive electrode sheet, negative electrode sheet, separator, electrolyte and aluminum-plastic film;
[0050] Among them, the positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the current collector. The positive electrode slurry solvent is NMP, the solid material content is 69%, the slurry viscosity is 8500mpa.s, and the solid material contains 96.5% of the six-series high-voltage ternary (Jinfuli: 06T7), 0.8% of the conductive agent LI-20, 1.2% of the conductive slurry (Haiwei Jiaye O2H017) and 1.5% of the binder PVDF; the positive electrode current collector is 12um aluminum foil;
[0051] The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the current collector, and the negative electrode current collector is a 6um copper foil;
[0052] The diaphragm is a three-layer diaphragm with a thickness of 15um, including a PE base film, a ceramic coating and a ceramic adhesive coating. The thickness of the PE base film is 9um, the thickness of the ceramic coating is 3um, and the thickness of the ceramic adhesive coating is 3um. The ceramic and ceramic adhesive are applied in separate coating processes.
[0053] The electrolyte lithium salt concentration is 1.5 mol / L, the solvent ratio is EC:EMC:PC:PA:EA=25:15:10:35:15, and 1.5% DTD additive is added;
[0054] The aluminum-plastic film is a heat-sealable aluminum-plastic film with a three-layer structure of nylon, aluminum and PP and a thickness of 0.088mm;
[0055] The preparation method of the soft-pack lithium-ion battery comprises the following specific steps:
[0056] 1) Preparation of positive electrode slurry and positive electrode sheet. The positive electrode sheet is prepared by using the positive electrode middle tab method and affixing high temperature resistant masking tape on the positive electrode tab. The specific structure is as shown in the attached Figure 1 As shown;
[0057] 2) Preparation of negative electrode slurry and negative electrode sheet;
[0058] 3) The material is sequentially subjected to core assembly, liquid injection, activation, formation and capacity separation to obtain a high-rate cycle high-voltage soft-pack lithium-ion battery, wherein a ceramic rubber diaphragm is used for winding during the core assembly, and after the winding is completed, the core needs to be subjected to a pressurized and heated short-circuit test and a pressurized low-temperature rapid cooling and shaping production, and the temperature of the pressurized and heated short-circuit test is 85±3°C, the time is 1min, and the surface pressure is 5±0.5kgf / cm 2 ; The temperature of pressurized low temperature rapid cooling is 10±3℃, the time is 1min, and the surface pressure is 6±0.5kgf / cm 2 , the actual set pressure calculation formula is as follows: set pressure = core width * core height - surface pressure;
[0059] in,
[0060] The preparation of the positive electrode slurry specifically includes the following steps:
[0061] (1-1) Weighing raw materials: weigh the raw materials according to the mass percentage of the positive electrode slurry;
[0062] (1-2) Dry powder mixing: Add the raw materials in the order of main material five-series or six-series high-voltage ternary 50%, conductive agent LI-20 100%, PVDF 100% and the remaining main materials, and stir the dry powder for 30 minutes to obtain a mixed dry powder;
[0063] (1-3) mud-like stirring: adding 28% by weight of NMP to the mixed dry powder and mud-like stirring to obtain a mud-like mixture;
[0064] (1-4) High viscosity stirring: Add the obtained muddy mixture to the conductive slurry and stir evenly, then add the remaining NMP to adjust the viscosity. After the viscosity is adjusted to 8500 mPa.s, degassing is performed to obtain the positive electrode slurry. The specific stirring process is shown in Table 4;
[0065] Table 4 Cathode slurry stirring process parameters
[0066]
[0067] Example 2
[0068] A highly efficient and stable negative electrode slurry for lithium batteries, wherein the negative electrode slurry solvent is deionized water and NMP (the amount of NMP added is 4% of the mass of the solid material), the solid material content is 49%, the slurry viscosity is 2950mpa.s, and the solid material contains 78% of graphite, 16.5% of silicon oxide, 1.5% of conductive agent LI-20, 0.05% of conductive slurry, 1.45% of CMC and 2.5% of suspending agent SBR;
[0069] The preparation of negative electrode slurry specifically includes the following steps:
[0070] The preparation of negative electrode slurry specifically includes the following steps:
[0071] (1) Weighing raw materials: weigh the raw materials according to the mass percentage of the negative electrode slurry;
[0072] (2) Preparation of glue solution: CMC and deionized water are added into the mixing barrel in a ratio of 1.4:98.6 and stirred. First, stir at low speed for 5 minutes, change the speed and stir for 10 minutes after cleaning, clean again, and then stir at high speed for 20 minutes. After high-speed stirring, observe that the glue solution is transparent and clear, and there are no glue particles in the glue solution. If there are residual undissolved glue particles in the glue solution, the glue application time is extended by 30-60 minutes accordingly. After the glue solution is qualified, vacuum degassing is carried out for 10 minutes before discharging. The final glue solution viscosity is 2500mpa.s.
[0073] (3) Preparation of graphite pre-slurry: Add graphite and 4 / 5 of the conductive agent into a slurry mixing barrel for dry powder stirring; then, add 2 / 5 of the glue and perform a first infiltration stirring; then, add 4 / 5 of the conductive slurry and perform a second infiltration stirring; finally, add deionized water to adjust the viscosity, and the final viscosity is 6200mpa.s. The specific stirring process is shown in Table 1;
[0074] (4) Preparation of silicon oxide pre-slurry: Add the silicon oxide and the remaining conductive agent into a slurry mixing barrel for dry powder stirring; then, add 1 / 12 of the glue solution and perform a first soaking stirring; then, add the remaining conductive slurry for a second soaking stirring; finally, add deionized water for viscosity adjustment, and the final viscosity is 6350 mPa.s. The specific stirring process is shown in Table 2;
[0075] (5) Liquid fusion: Add graphite pre-slurry and silica pre-slurry into a mixing barrel for liquid dissolution stirring; then, add the remaining glue solution and stir for dilute glue; then adjust the slurry viscosity by adding deionized water, and the final viscosity is 2950mPa.s; then, add the suspending agent SBR to the slurry after the viscosity adjustment and stir for suspension; finally, add NMP to the slurry after stirring and reverse degassing to obtain qualified negative electrode slurry. The specific stirring process is shown in Table 3.
[0076] A lithium battery was prepared using the negative electrode slurry prepared in Example 2:
[0077] Including positive electrode sheet, negative electrode sheet, separator, electrolyte and aluminum-plastic film;
[0078] Among them, the positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the current collector. The positive electrode slurry solvent is NMP, the solid material content is 72%, the slurry viscosity is 9200mpa.s, and the solid material contains 96% of six-series high-voltage ternary, 1.0% of conductive agent LI-20, 1.5% of conductive slurry and 1.5% of binder PVDF; the positive electrode current collector is 12um aluminum foil;
[0079] The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the current collector, and the negative electrode current collector is a 6um copper foil;
[0080] The diaphragm is a three-layer diaphragm with a thickness of 13um, including a PE base film, a ceramic coating and a ceramic adhesive coating. The thickness of the PE base film is 9um, the thickness of the ceramic coating is 2um, and the thickness of the ceramic adhesive coating is 2um. The ceramic and ceramic adhesive are applied in separate coating processes.
[0081] The electrolyte lithium salt concentration is 1.5 mol / L, the solvent ratio is EC:EMC:PC:PA:EA=25:15:10:35:15, and 1.5% DTD additive is added;
[0082] The aluminum-plastic film is a heat-sealable aluminum-plastic film with a three-layer structure of nylon, aluminum and PP and a thickness of 0.088mm;
[0083] The preparation method of the soft-pack lithium-ion battery comprises the following specific steps:
[0084] 1) Preparation of positive electrode slurry and positive electrode sheet. The positive electrode sheet is prepared by using the positive electrode middle tab method and affixing high temperature resistant masking tape on the positive electrode tab. The specific structure is as shown in the attached Figure 1 As shown;
[0085] 2) Preparation of negative electrode slurry and negative electrode sheet;
[0086] 3) The material is sequentially subjected to core assembly, liquid injection, activation, formation and capacity separation to obtain a high-rate cycle high-voltage soft-pack lithium-ion battery, wherein a ceramic rubber diaphragm is used for winding during the core assembly, and after the winding is completed, the core needs to be subjected to a pressurized and heated short-circuit test and a pressurized low-temperature rapid cooling and shaping production. The temperature of the pressurized and heated short-circuit test is 85±3°C, the time is 2min, and the surface pressure is 5±0.5kgf / cm 2 ; The temperature of pressurized low temperature rapid cooling is 10±3℃, the time is 2min, and the surface pressure is 6±0.5kgf / cm 2 , the actual set pressure calculation formula is as follows: set pressure = core width * core height - surface pressure;
[0087] The preparation of the positive electrode slurry specifically includes the following steps:
[0088] (1-1) Weighing raw materials: weigh the raw materials according to the mass percentage of the positive electrode slurry;
[0089] (1-2) Dry powder mixing: Add the raw materials in the order of main material five-series or six-series high-voltage ternary 50%, conductive agent 100%, PVDF 100% and remaining main materials, and stir for 30 minutes to obtain a mixed dry powder;
[0090] (1-3) mud-like stirring: adding 28% by weight of NMP to the mixed dry powder and mud-like stirring to obtain a mud-like mixture;
[0091] (1-4) High viscosity stirring: Add the obtained muddy mixture to the conductive slurry and stir evenly, then add the remaining NMP to adjust the viscosity. After the viscosity is adjusted to 9200 mPa.s, degassing is performed to obtain the positive electrode slurry. The specific stirring process is shown in Table 4;
[0092] Comparative Example 1
[0093] During the preparation of the lithium-ion battery, the negative electrode slurry was prepared by a rapid slurry mixing method (as shown in Table 5), and the other conditions were the same as those in Example 1;
[0094] Table 5 Process parameters of rapid slurry mixing method
[0095]
[0096] Comparative Example 2
[0097] Take the conventional battery with the same volume energy ratio on the market (5560100-5000mAh produced by Fengfan Co., Ltd.) for performance test and compare the performance data;
[0098] The batteries prepared in Example 1-2 and Comparative Example 1-2 were tested and compared, and the results are as follows:
[0099] Table 6 shows the high temperature short circuit test results of the batteries prepared in Examples 1-2 and Comparative Examples 1-2. It can be seen from the table that the batteries in Examples 1 and 2 prepared by the method of the present invention can meet the 55°C high temperature short circuit test, and the maximum temperature of the battery body during the high temperature short circuit process is relatively similar and lower than that of the batteries prepared in other schemes;
[0100] Table 6 High temperature short circuit test results of batteries prepared in Example 1-2 and Comparative Example 1-2
[0101]
[0102] like Figure 1The figure is a comparison diagram of the discharge curves of the batteries prepared in Examples 1-2 and Comparative Examples 1-2. It can be seen from the figure that the discharge platforms of the batteries in Examples 1 and 2 prepared according to the method of the present invention are similar and higher than the discharge platforms of the batteries in the other comparative examples;
[0103] like Figure 2 The figure is a cycle comparison curve diagram of the batteries prepared in Examples 1-2 and Comparative Examples 1-2. It can be seen from the figure that the cycle retention rates of the batteries in Examples 1 and 2 prepared according to the method of the present invention are similar and are better than those of the batteries in the other comparative examples;
[0104] like Figure 3 The figure is a rate comparison curve diagram of the batteries prepared in Examples 1-2 and Comparative Examples 1-2. It can be seen from the figure that the rate discharge performance of the batteries in Examples 1 and 2 prepared according to the method of the present invention is similar and the rate discharge performance is better than that of the batteries in the other comparative examples;
[0105] It can be concluded from the above that the method of the present invention can effectively improve the battery cycle performance, battery rate discharge performance, increase the battery discharge platform and improve battery safety, and expand the application range of lithium-ion batteries.
[0106] The various embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to in detail.
[0107] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A highly efficient and stable negative electrode slurry for lithium batteries, characterized in that: The negative electrode slurry comprises a solvent and a solid material, wherein the mass percentage of the solid material is 40-50%; The solid material comprises the following raw materials in percentage by mass: 77-82% of graphite, 13.6-17.2% of silicon oxide, 0.8-1.2% of conductive agent, 0.05-0.1% of conductive paste, 1.35-1.5% of sodium carboxymethyl cellulose and 2.2-3.0% of suspending agent.
2. The efficient and stable negative electrode slurry for lithium battery according to claim 1, characterized in that: The solvents are water and NMP, and the amount of NMP added is 1-4% of the mass of the solid material.
3. The efficient and stable negative electrode slurry for lithium battery according to claim 1, characterized in that: The viscosity of the negative electrode slurry is 2000-4000 mpa.s.
4. The efficient and stable negative electrode slurry for lithium battery according to claim 1, characterized in that: The suspending agent is SBR.
5. The method for preparing a highly efficient and stable negative electrode slurry for a lithium battery according to any one of claims 1 to 4, characterized in that: The specific steps include: (1) Weighing raw materials: weighing raw materials of negative electrode slurry according to the mass percentage; (2) Preparation of glue solution: CMC and water are mixed and then glued to obtain glue solution; (3) Preparation of graphite pre-slurry: After dry powder mixing of graphite and part of the conductive agent, part of the glue is added for primary infiltration and stirring; then part of the conductive slurry is added for secondary infiltration and stirring; finally, water is added for viscosity adjustment to 6000-6500 mPa.s to obtain graphite pre-slurry; (4) Preparation of silicon oxide pre-slurry: After dry powder mixing of silicon oxide and the remaining conductive agent, a portion of the glue solution is added for primary wetting and stirring; then the remaining conductive slurry is added for secondary wetting and stirring; finally, water is added for viscosity adjustment to 6000-6500 mPa.s to obtain silicon oxide pre-slurry; (5) Liquid fusion: The graphite pre-slurry and the silicon oxide pre-slurry are mixed and stirred for liquid dissolution. After completion, the remaining glue solution is added for dilute glue stirring, and then the water is added for viscosity adjustment to 2000-4000 mPa.s. Finally, a suspending agent is added in sequence for suspension stirring and NMP is added for inversion degassing to obtain a negative electrode slurry.
6. The method for preparing a highly efficient and stable negative electrode slurry for a lithium battery according to claim 5, characterized in that: The viscosity of the glue in step (2) is 2000-4000 mPa.s.
7. The method for preparing a highly efficient and stable negative electrode slurry for a lithium battery according to claim 5, characterized in that: In step (3), the amount of the conductive agent added is 4 / 5-5 / 6 of the total amount, the amount of the glue added is 2 / 5-5 / 12 of the total amount, and the amount of the conductive paste added is 4 / 5-5 / 6 of the total amount.
8. The method for preparing a highly efficient and stable negative electrode slurry for a lithium battery according to claim 5, characterized in that: The amount of the glue added in step (4) is 1 / 12-1 / 10 of the total amount.
9. Use of a highly efficient and stable negative electrode slurry for lithium batteries according to any one of claims 1 to 4 or a highly efficient and stable negative electrode slurry for lithium batteries obtained by the preparation method according to any one of claims 5 to 8 in preparing negative electrode sheets.
10. Use of the efficient and stable negative electrode slurry for lithium batteries according to any one of claims 1 to 4 or the efficient and stable negative electrode slurry for lithium batteries obtained by the preparation method according to any one of claims 5 to 8 in preparing lithium batteries.
